Exploring the Bioaccessibility of Roasted Japanese Green Tea: Impact of Simulated Gastrointestinal Digestion - Wei Qin; Sunantha Ketnawa (Foods)
In this study, the effects were explored of digestive enzymes and pH on the bioaccessibility of polyphenols, flavonoids, and antioxidant activities in Hojicha (roasted green tea, RT) infusions during simulated in vitro digestion. Roasting modifies its polyphenolic profile and reduces bitterness, making it a popular variation of green tea. In this study, RT was used for assessing how the roasting-induced changes influenced the tea’s bioaccessibility and stability under digestive conditions. A two-step gastrointestinal digestion model was applied to mimic real digestion. Total polyphenol content (TPC), total flavonoid content (TFC), and antioxidant activity (DPPH, ABTS, FRAP, and MIC) were measured at different digestion stages. Gastric conditions led to a 2.07-fold reduction in TPC and a 4.27-fold reduction in TFC. Digestive enzymes enhanced bioactive compound stability, with TPC and TFC bioaccessibility reaching 56% and 25% in the simulated digestion with digestive enzymes (MD) group, compared to 52% and 20% in the without digestive enzymes (WOE) group. Antioxidant activities were also better preserved, with antioxidant activity retention at 31% in the MD samples versus 19% in the WOE. These findings emphasize the key role of digestive enzymes in maintaining the antioxidant potential of roasted green tea during digestion, providing insight into future research on roasting methods and tea functionality for product development.